Proceedings of the 27th Symposium on Integrated Circuits and Systems Design 2014
DOI: 10.1145/2660540.2661000
|View full text |Cite
|
Sign up to set email alerts
|

Performance and Impact of Process Variations in Tunnel-FET Ultra-Low Voltage Digital Circuits

Abstract: In this paper, the potential of Tunnel FETs (TFETs) for ultra-low power operation is investigated in the context of digital circuits operating below 500 mV. A comparative analysis of TFETs and SOI CMOS in 32 nm technology is performed through deviceand circuit-level simulations, based on a unitary simulation framework where all devices are fairly designed for the same (low) voltage range and the same device-level targets.The performance is evaluated through figures of merit at device and circuit level, quantif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0
1

Year Published

2017
2017
2018
2018

Publication Types

Select...
2
2

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 20 publications
0
2
0
1
Order By: Relevance
“…Due to the promising advantages of individual TFETs, basic circuits have also been analyzed in recent papers [18,19]. For instance, digital configurations such as multiplexers and inverters have been studied, mainly by simulations [20,21], with a couple of papers presenting experimental data as well [22,23].…”
Section: Introductionmentioning
confidence: 99%
“…Due to the promising advantages of individual TFETs, basic circuits have also been analyzed in recent papers [18,19]. For instance, digital configurations such as multiplexers and inverters have been studied, mainly by simulations [20,21], with a couple of papers presenting experimental data as well [22,23].…”
Section: Introductionmentioning
confidence: 99%
“…Considering the mentioned advantages of TFETs individual behavior, recent studies haves shown how basic circuits may be improved as well [20][21][22]. Digital configurations such as inverters and multiplexers have been analyzed, with a vast majority of studies based on simulations [23,24], but also a few with experimental data [25,26].…”
Section: Introductionmentioning
confidence: 99%
“…the inverse sub-threshold slope (SS) is limited by 60 mV/ dec (at room temperature), and therefore a decrease in V DD results in an exponential increase of sub-threshold leakage current according to the equation expressed by (1.1) [20]:…”
Section: Tunnel Fets As a Key Technology For Energy Harvestingmentioning
confidence: 99%
“…Adapted from [24]. __________________________________________ 26 (d) considering N A =1×10 20 cm -3 and N A =1×10 19 cm -3 and the TFET device in on-state (V DS =V GS =1V). _______ 45 TFET [4] and broken gap AlGaSb/InAs TFET [5].…”
mentioning
confidence: 99%